(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
This paper explores the dynamic interplay between the concepts of scale and in-novation, emphasizing the multifaceted and interdisciplinary nature of their re-lationship. Drawing insights from human geography, political ecology, and eco-nomics, the study delves into how scale—understood as hierarchical, relational, and fluid—shapes and is shaped by innovative processes. It argues that innovation is not only about the introduction of new products or processes but also about their diffusion and adaptation across various scales. By examining theories like “scale jumping” and “scale bending,” the paper illustrates how organizations and innovators navigate different levels of operation to optimize resources, align with socio-political contexts, and address market demands. Through case studies the paper highlights the relational and strategic dimensions of scale in innovation. It also addresses challenges such as resource standardization, control dynamics, and localized policy needs. Ultimately, the paper underscores the critical role of scale as a tool for fostering sustainable and inclusive innovation, advocating for a nuanced understanding of its implications in a globalized world.